The Questions of Development of Fiberoptic Sensors for Measuring Pressure with Improved Metrological and Operational Characteristics - Yurchenko A. V. Aleksey Vasilievich; Alkina A. Aliya; Mekhtiyev (Mekhtiev) A. Ali; Bulatbayev F. Felikc; Neshina E. Elena (2016, 2016)
Title screen